ANALISIS DAYA DUKUNG SPUN PILE BERDASARKAN DATA KALENDERING DAN STANDARD PENETRATION TEST (SPT) - Hutabarat, Daniel Efriand; Yelvi, Yelvi (Politeknik Negeri Jakarta, 2025)
The construction of the Serang–Panimbang Toll Road Section III Phase 2 Package 3 was part of a National Strategic Project requiring a strong foundation to overcome soil settlement. Spun piles were used as the primary foundation to resist both vertical and horizontal loads. This study aimed to determine axial bearing capacity based on pile driving (calendering) and SPT data analysis, calculate lateral bearing capacity, and evaluate pile settlement and displacement. Pile driving analysis showed varying capacities, with the lowest value from the Navy-McKay formula (371.782 kN) and the highest from the WIKA formula (926.061 kN). The Meyerhof α formula from SPT analysis produced the highest axial capacity (1052.162 kN). Lateral bearing capacity based on Broms (1965) exceeded allowable limits in both sand (9608.429 kN) and clay (6272.101 kN). Pile settlement occurred as a response to structural loads acting on the foundation and was influenced by the physical and mechanical properties of the supporting soil beneath. Based on elastic analysis using Vesic’s method (1967), the maximum settlement was (25.224 mm), occurring at the interaction zone between the spun pile and dominant soil layers at foundation depth. This value remained within the safe limit according to SNI 8460:2017. Overall, the spun pile foundation proved effective in maintaining stability under vertical and horizontal force while ensuring structural integrity and sustainability against potential settlement and displacement.